Rethinking Methodologies: Implications for Research on International Students - Dhruba Neupane (University of Windsor, 2022)
Research in international student success, satisfaction, and challenges seems still to be constructed around the colonial, imperial paradigm. Informed by deficit models of language, culture, and literacy teaching, such research portrays international students' challenges in terms of deficiency; discounts other languages, cultures, and literacy education; and reinstitutes the progressive and paternalistic role of the West, reifying its linguistic and cultural superiority. This essay interrupts the still dominant narrative that recreates the old binaries in two ways: (a) It frontloads the need to adopt strength-based approaches to counter dominant methodological paradigms from which much of knowledge about culturally and linguistically different/disadvantaged (CLDI) students is derived, and (b) based on my own ethnographic study on a South Asian immigrant population in Canada, it demonstrates that what the old paradigm views as deficits can and should be the very measures from which to appraise student success and satisfaction. Accordingly, the article's main objectives are twofold: (a) expose the weaknesses of the deficit models of language, culture, and competence and (b) stress the need to reshape international student studies in higher education as a field of inquiry by foregrounding appreciative models and methodologies.